The Creation of the World - A Galactic Event Beyond Human Grasp - Gurevitz, Michael; Dagan, Roee (European Journal of Applied Sciences, 2024)
The Big Bang theory, first raised in 1931 by the Belgian physicist and catholic priest Georges Lemaître, and supported ever since by most astrophysicists, depicts a 13.8 billion years-old galactic event, wherein an enormous quantity of light energy that aggregated within an infinitely hot and dense ‘Singularity’ dot, suddently inflated and stretched, spreading tremendous amounts of heat and gas that were the primordial components of the universe. Over time that began at the inflation moment (A. Einstein), the extremely hot matter cooled enough to form galaxies (stars surrounded by planets in orbits dictated by their gravitational interactions). Amazingly, subsequent to the inflationary moment, the universe continues to expand in an accelerating manner.